2013
DOI: 10.1080/10286020.2012.762358
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside attenuates myocardial ischemia–reperfusion injury via PI3K/Akt signaling pathway

Abstract: To investigate the cardioprotective effects of salidroside on myocardial ischemia-reperfusion injury (IRI) in rabbits and the underlying action mechanisms in PI3K/Akt signaling pathway, a rabbit ischemia/reperfusion model was created by ligating the left anterior descending coronary arterial branch for 30 min and by releasing the ligature to allow reperfusion for 120 min. Salidroside or salidroside+PI3K inhibitor (LY294002) was administered via intracoronary injections at the onset of reperfusion. Apoptosis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…CHOP sensitizes cells to ER stress-induced apoptosis by causing an imbalance of Bcl-2 family members and then promoting cytochrome c release from the mitochondria to activate the apoptotic cascade ( 26 ). The results of the present study demonstrated that salidroside treatment reversed the H/R-induced upregulation of Bax expression and downregulation of Bcl-2 expression in H9c2 cells, which is consistent with the results of previous studies ( 29 , 38 ). These results indicate that salidroside may inhibit myocardial I/R injury by attenuating ER stress or ER stress-induced apoptosis by mitigating the mitochondria-dependent apoptotic pathway.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…CHOP sensitizes cells to ER stress-induced apoptosis by causing an imbalance of Bcl-2 family members and then promoting cytochrome c release from the mitochondria to activate the apoptotic cascade ( 26 ). The results of the present study demonstrated that salidroside treatment reversed the H/R-induced upregulation of Bax expression and downregulation of Bcl-2 expression in H9c2 cells, which is consistent with the results of previous studies ( 29 , 38 ). These results indicate that salidroside may inhibit myocardial I/R injury by attenuating ER stress or ER stress-induced apoptosis by mitigating the mitochondria-dependent apoptotic pathway.…”
Section: Discussionsupporting
confidence: 93%
“…It has been demonstrated that ER stress contributes to cardiomyocyte apoptosis, which results in myocardial I/R and suppressing ER stress-associated apoptosis may be a critical therapeutic approach for treating myocardial I/R injury ( 19 , 28 , 29 ). Salidroside is an active ingredient extracted from Rhodiola rosea L ., which has various pharmacological functions, including anti-apoptosis, anti-oxidation and cardioprotection ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Salidroside (SAL), an effective extracted component from R. crenulata, is a traditional Chinese medicine that has been recognized as a plant-derived adaptogen capable of maintaining physiological homeostasis upon exposure to stress. Accumulating evidence suggests that SAL has protective effects on many cardiac diseases such as myocardial I/R injury (Xu et al, 2013). Recently, Ping and colleagues have demonstrated that SAL improves myocardial mitochondrial respiratory function by stimulating the expression of PGC-1α-NRF-1/NRF-2 pathway during cardioprotection (Ping et al, 2015).…”
Section: Dox-induced Cardiomyopathymentioning
confidence: 99%
“…Salidroside (SAL) is an effective extract component from R. crenulata . Many studies have found that SAL had protective effects on myocardial ischemia reperfusion [ 7 ], myocardial hypoxia [ 8 ], and myocardial injury [ 9 ]. Our previous research has suggested that SAL could improve hypoxia-induced cardiac myocyte energy metabolism by increasing the intracellular activity of the respiratory enzyme succinate dehydrogenase (SDH) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%